DEMOGRAPHIC VARIABLES OF SAFETY RISK BEHAVOURS AMONG SECONDARY SCHOOL STUDENTS IN AGBANI EDUCATION ZONE. - Ochiaka , Raphael E; Okoli, Susan N (Global Journal of Medical and Health Science, 2024)
The study examined demographic variables of safety risk behaviours among secondary school adolescents in Agbani Education Zone, Enugu State. Three research questions and one null hypothesis guided the study. A descriptive survey design was adopted for the study. A sample of 388 secondary school adolescents which was drawn from a population of 13,105 secondary schools in Agbani Education Zone was used for the study. Structured questionnaire titled “Demographic variable of Safety Risk Behaviour Questionnaire (DVSRBQ)” which was validated by three experts, two from the Department of Human Kinetic and Health Education and one from Maths and Computer Department was used fir data collection. The instrument yielded a reliability coefficient index of .78 showing that it is reliable. Mean statistics was used to analyse data collected in line with research questions while t-test statistic was used to test the null hypothesis at .05 level of significance. The findings of the study were; that secondary school adolescents in Agbani Education Zone were involved in safety risk behavior to a low extent, both male and female secondary school adolescents, both urban and rural secondary school adolescents in Agbani Education Zone were involved in safety risk behaviours to a low extent. The involvement of secondary school adolescents in safety risk behaviour is dependent on gender. It was concluded that secondary school adolescents in Agbani Education Zone involved in safety risk behaviour to a low extent. Thus, it was recommended among others that the state government through the PPSMB should organize orientation, Seminars and workshops on the consequences of safety risk behaviours for secondary school adolescents